Species delimitation and taxonomic revision of Abana Distant, 1908 (Hemiptera: Cicadellidae: Proconiini): Intraspecific color variation and pseudocryptic diversity in Andean sharpshooters - Sauceda-V, Jefferson; Malenovský, Igor; Takiya, Daniela M. (Zootaxa, 2025)
The Neotropical proconiine sharpshooter genus Abana includes six previously described species, some of which have nearly identical male genitalia but differ in coloration. The taxonomy of the genus is here revised based on comparative morphological study and phylogenetic analysis of partial mitochondrial COI sequences coupled with the following molecular species delimitation methods: ABGD, ASAP, PTP (including bPTP) and GMYC. Phylogenies for the implementation of the tree-based methods for species delimitation were hypothesized based on maximum likelihood and Bayesian inference reconstructions. The results of the molecular species delimitation showed that A. horvathi is a species complex with sexual dimorphism, which is reported for the first time. In addition, two very different color morphotypes were found within A. tissa, recognized as the same species by all delimitation methods. The results of the revision, including photographs of the primary types of all nominal species, support the validity of the six previously known species of Abana. Seven new species are described from Colombia, Panama and Peru: Abana amazonica Sauceda-V & Takiya, sp. nov., A. colombiana Sauceda-V & Takiya, sp. nov., A. confusa Sauceda-V & Takiya, sp. nov., A. inornata Sauceda-V & Takiya, sp. nov., A. minuta Sauceda-V & Takiya, sp. nov., A. ochracea Sauceda-V & Takiya, sp. nov., and A. rufifrons Sauceda-V & Takiya, sp. nov. Abana sonora Melichar, stat. rev. is removed from synonymy with A. horvathi and placed as a valid species outside the genus as Cicadellini incertae sedis. A lectotype is designated for Abana regia Melichar to stabilize the nomenclature. Abana tissa is recorded for the first time in Colombia and the morphology of the last instar nymph of this species is also described and documented for the first time. A key to the species and new geographical records as well as a distribution map are also provided.